2018
DOI: 10.1177/0954405418815365
|View full text |Cite
|
Sign up to set email alerts
|

Heat flux distribution and temperature prediction model for dry and wet cylindrical plunge grinding

Abstract: The grinding heat is generally partitioned into the workpiece, wheel, chips and fluid in grinding process. The total amount of heat flux entering into the workpiece greatly affects the final workpiece surface temperature, which may cause undesirable workpiece burn. Moreover, the variable grinding chip thickness and fluid injection speed along the grinding contact zone could substantially change the specific energy and the shape of the heat source correspondingly. In this article, a Weibull heat flux distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The triangular heat flux distribution was more consistent with the measured data of temperature than other distribution for plane grinding based on the inverse heat transfer analysis [8]. Pang et al [9] proposed a shape parameter which determined the heat flux distribution and the value was fitted against experimental data. The investigation indicated that the shape of heat source influenced the grinding temperature significantly.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The triangular heat flux distribution was more consistent with the measured data of temperature than other distribution for plane grinding based on the inverse heat transfer analysis [8]. Pang et al [9] proposed a shape parameter which determined the heat flux distribution and the value was fitted against experimental data. The investigation indicated that the shape of heat source influenced the grinding temperature significantly.…”
Section: Introductionsupporting
confidence: 65%
“…The specific power to chips e ch is assumed to be close to the limiting chip energy, and e ch is approximately 6 J/mm 3 for aluminum alloy material [30]. The heat flux to chips q ch can be expressed by equation (9), which is also related to the depth of cut, feedrate, and contact length.…”
Section: Modeling the Micro-grinding Temperaturementioning
confidence: 99%
“…Dai et al 12 proposed a Chi-square heat source model based on the material removal mechanism of the cup wheel, and experimental verification showed that the model significantly improved the accuracy of the prediction of the temperature field of cup wheel. Pang et al 13,14 proposed the Weibull heat flux density distribution model in the study of cylindrical grinding, considering the influence of the thickness of the grinding chips and the injection speed of the grinding fluid on the shape of the heat source and the heat distribution ratio. And it was found in the experiment that with the continuous increase of the wheel speed, the increasing trend of the grinding temperature become slower.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike conventional transverse cylindrical grinding, 36 the roller grinding possesses more special quality requirements, for example, roller profile accuracy and visual gloss defect. The roller profile shown in Figure 1(b) can be expressed as z = f ( x ), where f represents the fitting function, x and z are the displacements along the X and Z axes, respectively, and the range of the highest power of z is from 5 to 12.…”
Section: Introductionmentioning
confidence: 99%